2013
DOI: 10.1111/ped.12033
|View full text |Cite
|
Sign up to set email alerts
|

Complications of peripherally inserted central venous catheter in Japanese neonatal intensive care units

Abstract: The incidence of cardiac tamponade was rare in this multicenter prospective study. Longer duration and proximal placement may be risk factors for PICC complications. In this cohort, the CR-BSI rate was low irrespective of the degree of barrier precautions at insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 22 publications
3
34
0
6
Order By: Relevance
“…The incidence of this complication for adults is unknown. Although our patient developed no problems during a one-day cannulation, it is important to recognize the possibility of PICC placement in the left paramediastinal space and its consequences even with ultrasound guidance [3,4]. This emphasizes the importance of radiography after insertion.…”
Section: Discussionmentioning
confidence: 73%
“…The incidence of this complication for adults is unknown. Although our patient developed no problems during a one-day cannulation, it is important to recognize the possibility of PICC placement in the left paramediastinal space and its consequences even with ultrasound guidance [3,4]. This emphasizes the importance of radiography after insertion.…”
Section: Discussionmentioning
confidence: 73%
“…1,2,[10][11][12][13][14] The cumulative risk of CLABSI increases the longer a PICC remains in place, but it is unknown whether the daily risk of CLABSIs increases over the dwell time of the catheter. 15 A recent study of neonates suggested that for PICCs that remained indwelling for .35 days, the risk of CLABSIs increased by 33% per additional day the catheter was in place.…”
Section: Articlementioning
confidence: 99%
“…[1][2][3][4] A prospective cohort study of 19 NICUs in Japan over a 2-year period reported an incidence of 0.1%. 1 In a nationwide survey from Britain, the incidence of pericardial effusion or cardiac tamponade was 0.18%.…”
mentioning
confidence: 99%